Pituitary enlargement and hypopituitarism in patient with lung cancer treated with immune checkpoint inhibitors: Metastasis or hypophysitis? Role of imaging - Pier Paolo Arcuri, MD; Vincenzo Aiello, MD; Simonetta Antonelli, MD; Simona Roccia, MD; Francesco Manti, MD; Domenico Laganà, MD (Radiology Case Reports)
Pituitary gland metastasis is an unusual event, and pituitary metastasis from lung adenocarcinoma is extremely rare and associated with poor prognosis. To date, approximately 16 cases have been reported. Symptoms of these lesions can mimic hypophysitis, that is a possible immune-related adverse event of ICIs (Immune Checkpoint Inhibitors). Pituitary metastases and hypophisitis are life-threatening diseases and making differential diagnosis is important, because therapy of these conditions is quite different. Differentiating a condition from the other one is difficult, because many imaging features are not specific. In this presented case, cross-sectional imaging, in particular Magnetic Resonance Imaging (MRI), has revealed itself helpful to suggest the diagnosis of pituitary metastasis rather than hypophysitis.